The role of the Interview Manager (IM) in UK policing: perceptions and experiences of the IM when deployed in high stakes crime investigations - Vaughan, Martin (Policing and society, 2025)
The last 30 years have seen a dramatic shift in investigative interview training in the United Kingdom (UK) as a result of miscarriages of justice cases featuring vulnerable suspects. In 2001, the UK Police adopted a five-tiered approach to investigative interviewing, with Tier 1 for new recruits through to Tier 5 for interview managers (IMs). The IM is responsible for overseeing strategic decisions with regard to the investigative interviewing process. Even though the role of an IM has been in existence for over twenty years, it is one of the most under-researched aspects of investigative interviewing. The aim of the current paper is to present an oversight of the role of an IM in UK policing using a self-report questionnaire, presenting the responses of 53 UK police IMs’ perceptions of their role in high-stakes crime investigations. Content analysis was carried out on the responses and revealed that IMs are most frequently deployed to murder investigations, followed by serious assaults, then sexual offences. However, not all of the respondents had received the pre-requisite training for the role. Nevertheless, the IMs broadly agreed that the senior investigating officer respected the advice provided by the IM, though without fully understanding what the role entailed. IMs unanimously said the role was crucial to high-stakes investigations and presented their perceptions of the skills, qualities and knowledge that IMs require to perform the role. Finally, future directions of research in this area are outlined.